Digitalization of Village Services in the VUCA Era: A Systematic Literature Review: Digitalisasi Pelayanan Desa di Era VUCA: Tinjauan Literatur Sistematis - Lailul Mursyidah; Hendra Sukmana; Isnaini Rodiyah; Ahmad Riyadh Umar Balahmar; Eni Rustianingsih (Universitas Muhammadiyah Sidoarjo, 2026)
Digital transformation in the public sector is a crucial strategy for improving the quality of public services and strengthening governance in the VUCA (Volatile, Uncertain, Complex, and Ambiguous) era. Village governments, as the government units closest to the community, play a strategic role in providing basic administrative services. This article aims to examine SIPRAJA as a form of village service digitalization from a VUCA perspective through a systematic literature review. The research data was obtained from scientific articles indexed by Scopus, ScienceDirect, and Google Scholar from 2015 to 2024. The study results indicate that village service digitalization plays a significant role in improving service efficiency, government transparency, and participation in village governance. However, the implementation of village digitalization still faces various challenges, such as limited digital infrastructure and literacy gaps.